O regramento dos honorários advocatícios no CPC/15 - Mendonça Neto, Delosmar Domingos de (2019)
The importance of legal fees, as will be seen below, goes beyond the sphere of interests of the professionals who survive it. Around the subject there is a true range of interested parties in the faithful compliance with the legal dictates related to the matter. The legislative change suffered by the Brazilian legal system has given rise to the urgent need to understand, in essence, the legal fees succumbencial. In this sense, we tried to work on the new regulation given by CPC / 15 to the theme. The focus of study lies in the changes brought by the procedural law. Those who think that these funds are static and do not dialogue with institutes of the most diverse within the law are deceived. It will be tried to demonstrate the relation between the central axis of studies and several other subjects that can (or not) come to raise to the lawyer the right to receive fees. For this, a bibliographical research was done in the national and foreign doctrine in order to synthesize the newly presented thoughts. From the above, a true metamorphosis in the subject was observed that, depending on the inserted context, behaves in a totally different way. The interrelation of funds with the most varied institutes of the legal system makes the study of the subject practical and interesting, besides representing a true worship a noble profession that has the mischief to bring justice where it does not exist